Leak-Before-Break methodology applied to different piping materials: a performance evaluation (Fracture and Structural Integrity, 2019)
This paper presents a study of the application of Leak-Before-Break (LBB) to nuclear piping using three different materials. Based on the fracture mechanics, the LBB concept considers that a leakage from a crack can be detected before it reaches a critical size that implies the pipe failure, that is, the LBB analysis demonstrates through a technical justification that the probability of pipe rupture is extremely low. Among the aspects that involve the application of LBB, the main ones are: the definition of the material properties, which are extracted through tensile and fracture tests; the leakage analysis, which determines the rate of leakage due to the presence of a through-wall crack; and the analysis that verifies if the crack is stable considering the failure modes by ductile tear and plastic collapse. The materials SA-508 Cl. 3, SA-106 Gr. B and SA-376-TP304 were evaluated in relation to their performances for LBB. Data extracted from literature cases were used for the materials properties, and for the geometry and loadings of the pipe, all corresponding to the primary circuit of a PWR reactor. After application of the LBB, it was verified that all three materials met the limits established in the methodology. SA-508 Cl. 3 and SA-376-TP304 steels showed the best performance for ductile tear failure and plastic collapse failure, respectively, and SA-106 Gr. B steel had the lowest performance in both. All three materials presented plastic collapse as the most likely failure mode. In general, SA-376-TP304 steel obtained the best performance for the LBB among the three materials evaluated in this work.
Keywords: Leak-Before-Break; LBB; Piping material; Material performance; PWR reactor; Fracture mechanics